2015
DOI: 10.1111/are.12950
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community of Pacific abalone (Haliotis discus hannai) juveniles during a disease outbreak in South China

Abstract: A mass mortality of farmed juvenile abalones (Haliotis discus hannai) occurred in South China in December of 2012. Combined traditional culturing with terminal restriction fragment length polymorphism (T-RFLP) methods, microbial communities associated with juvenile abalones were investigated under different survival conditions, including healthy (HA) and moribund (HM) abalones in the healthy pond with low mortalities, and healthy (DA) and moribund (DM) abalones in the diseased pond with a high mortality rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Similar results were also found for culture of clams (Kwan and Bolch 2015). It was also shown that an effective balance of microbial populations included in the same community ensures the final rearing success (Verschuere et al 1997;Kwan and Bolch 2015;Shi et al 2017). Recently, it has been proved that the intestinal microbiome, highly diverse, of octopus paralarvae reared in captivity and feed with Artemia is rapidly become less diverse and is mainly suggested as a consequence of culture conditions (Roura et al 2017).…”
Section: Potential Pathogenic Bacteria For Larval Development Stagessupporting
confidence: 54%
“…Similar results were also found for culture of clams (Kwan and Bolch 2015). It was also shown that an effective balance of microbial populations included in the same community ensures the final rearing success (Verschuere et al 1997;Kwan and Bolch 2015;Shi et al 2017). Recently, it has been proved that the intestinal microbiome, highly diverse, of octopus paralarvae reared in captivity and feed with Artemia is rapidly become less diverse and is mainly suggested as a consequence of culture conditions (Roura et al 2017).…”
Section: Potential Pathogenic Bacteria For Larval Development Stagessupporting
confidence: 54%
“…Previous analyses of healthy and diseased juvenile abalone suggested mass mortality events might be caused by changes in the microbial community and understanding the dynamics would provide another approach in the understanding such disease outbreaks (Shi et al., 2017). Vibrio species were also identified in the moribund abalone taken from healthy ponds in Shi's study.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional morphological and biochemical methods for bacterial identification have been replaced by sequencing. Colony hybridization (Tanaka et al., 2003), sequencing of the cloned 16S rDNA amplicons (Tanaka et al., 2004), denaturing gradient gel electrophoresis (DGGE) fingerprinting (Huang et al., 2010; Zhao et al., 2012), 16S rRNA gene clone libraries (Iehata et al., 2014), restriction fragment length polymorphism (T‐RFLP) methods (Shi et al., 2017), 16S sRNA gene MiSeq paired‐end sequencing (Gobet et al., 2018) and pyrosequencing of 16S rRNA genes (Zhao et al., 2018) have been used for abalone‐related sequencing. Most of the mentioned studies focus on the gastrointestinal microbiome; only Gobet et al included the “gonado‐digestive” gland probably because of the difficulty of excision of this organ.…”
Section: Introductionmentioning
confidence: 99%
“…Bivalve mollusks and gastropods have both an open circulatory system [5], and therefore bacteria and other contaminants can be expected in all organs and tissues, independently of the different feeding habits. Despite this biological evidence, the microbiology of marine gastropods has been poorly investigated, except few studies concerning disease outbreaks of Abalone, reporting high bacterial contamination of tissues also in healthy animals [42], and the study of Cheng et al [43] reporting high contamination of the gastropod Niotha clathrata muscle by Vibrio spp. (6-8 log 10 CFU g −1 ).…”
Section: Discussionmentioning
confidence: 99%